PD-L1 mediated the differentiation of tumor-infiltrating CD19+ B lymphocytes and T cells in Invasive breast cancer - Guan, Honggeng; Lan, Yang; Wan, Yuqiu; Wang, Qin; Wang, Cheng; Xu, Longjiang; Chen, Yongjing; Liu, Wenting; Zhang, Xueguang; Li, Yecheng; Gu, Yongping; Wang, Zemin; et al. (Oncoimmunology, 2016)
Accumulating evidence suggests that B cells play important roles in inhibiting the immune response in autoimmune disorders and human tumors as well as murine tumor models. In an effort to explore the role of B cells in human breast cancer etiology, we examined the presence of CD19 + B lymphocytes in 134 cases of invasive breast carcinoma (IBCa) and 31 breast fibroadenoma, and assessed its relationship with PD-L1 (programmed death-ligand 1) expression in breast cancer. We found that the density of CD19 + B lymphocytes was higher in IBCa compared with fibroadenoma, and significantly associated with increasing tumor grade, negative estrogen status. Similar findings were observed for the expression of IL-10 in IBCa. Meanwhile, CD19 + B lymphocytes were shown to be highly coincident with PD-L1 and IL-10 in IBCa. We further demonstrated that CD19 + B cells can differentiate into CD19 + CD24 + CD38 + B cells when co-cultured with PD-L1 hi MDA-MB231 cells. In addition, the percentage of CD19 + CD24 + CD38 + B cells was higher in breast tissue and peripheral blood cells of IBCa patients than that of benign tumor and health individuals. And CD19 + CD24 + CD38 + B cells were found to be IL-10 secreting B cells. Finally, we showed that CD19 + B cells from IBCa patients but not healthy individuals induced formation of CD4 + CD25 + Foxp3 + T cells when co-cultured with T cells from IBCa patients and healthy subjects (80.4% and 30.8% respectively). The induction of CD4 + CD25 + Foxp3 + T cells by CD19 + B cells was further shown to be mediated by PD-L1. Together, these results are suggestive of a role for CD19 + B lymphocytes in immune suppression and tumor evasion via PD-L1 in breast cancer.